2020
DOI: 10.3390/plants9040473
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphite Dehydrogenase Variant with Promiscuous Access to Nicotinamide Cofactor Pools Sustains Fast Phosphite-Dependent Growth of Transplastomic Chlamydomonas reinhardtii

Abstract: Heterologous expression of the NAD+-dependent phosphite dehydrogenase (PTXD) bacterial enzyme from Pseudomonas stutzerii enables selective growth of transgenic organisms by using phosphite as sole phosphorous source. Combining phosphite fertilization with nuclear expression of the ptxD transgene was shown to be an alternative to herbicides in controlling weeds and contamination of algal cultures. Chloroplast expression of ptxD in Chlamydomonas reinhardtii was proposed as an environmentally friendly alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…Consequently, ptxD/Phi selection can be used as a universal marker to transform C. reinhardtii wild-type microorganisms on medium containing Phi as a major source of P (Changko et al, 2020;Kanda et al, 2014). Combining phosphite fertilization with expression of the nuclear transgene ptxD provided an ideal substitute for herbicides in controlling weeds and pollution of algal cultures (Cutolo et al, 2020).…”
Section: Ptxd /Phi As Selectable Marker System In Microorganisms For Biological Contamination Control In Cultivation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, ptxD/Phi selection can be used as a universal marker to transform C. reinhardtii wild-type microorganisms on medium containing Phi as a major source of P (Changko et al, 2020;Kanda et al, 2014). Combining phosphite fertilization with expression of the nuclear transgene ptxD provided an ideal substitute for herbicides in controlling weeds and pollution of algal cultures (Cutolo et al, 2020).…”
Section: Ptxd /Phi As Selectable Marker System In Microorganisms For Biological Contamination Control In Cultivation Systemsmentioning
confidence: 99%
“…Chloroplast expression of ptxD in Chlamydomonas reinhardtii has been proposed as a more environmentally friendly substitute for antibiotic resistance genes in plastid transformation (Day & Goldschmidt-Clermont, 2011). Transplastomic genotypes expressing the mutant PTXD type utilized NADP+ and NAD + to convert Phi to Pi more efficiently and evolved more rapidly than those expressing the wild-type protein (Cutolo et al, 2020). Loera-Quezada et al (2016) reported that the production of genetically engineered microalgae capable of metabolizing Phi is a viable approach for developing a successful scheme for managing biological contaminants in microalgal development that can be combined with established biological and molecular strategies.…”
Section: Ptxd /Phi As Selectable Marker System In Microorganisms For Biological Contamination Control In Cultivation Systemsmentioning
confidence: 99%
“…One strategy for reducing contamination of algal cultures is the introduction of metabolic capacity for metabolism of inorganic phosphite as a phosphorous source. This has been shown in numerous organisms, including C. reinhardtii , to reduce contamination and act as a selection agent (López-Arredondo and Herrera-Estrella, 2012; Loera-Quezada et al, 2016; Changko et al, 2020; Cutolo et al, 2020; Dahlin and Guarnieri, 2022). Engineered expression of Pseudomonas stutzeri WM88 phosphite NAD+ oxidoreductase ptxD from either the chloroplast or nuclear genomes of algae has been shown to confer the ability to metabolize phosphite (López-Arredondo and Herrera-Estrella, 2012; Changko et al, 2020; Cutolo et al, 2020; Dahlin and Guarnieri, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…New technologies are developed such as the use of alternative source of phosphorus in order to control the contamination, for example the use phosphite deydrogenase (PtXD) that catalyzes the conversion of phosphite in phosphate [14]. Many Chlamydomonas strains have been produced expressing nuclear or chloroplastic PtxD [15,16]. There are many works in literature in which new strategies in tuning photosynthesis are developed.…”
Section: Introductionmentioning
confidence: 99%